Nilai-Nilai Pendidikan Karakter untuk Anak Usia Dini dalam Film “Adit & Sopo Jarwo” - Hidayatulloh, M. Agung (PIAUD Universitas Islam Negeri Sunan Kudus, 2017)
This article explores the values of character education for early children in the film Adit & Sopo Jarwo. This qualitative descriptive study analyzes the contents of the four episodes that were randomly selected. The study found that the values of character education for early children based on four episodes of the film Adit & Sopo Jarwo are religious, hard working, independent, friendly and communicative, honest, social care, creative, discipline, honoring of achievement, and responsibility.